STUDY OF EICHORNIA CRASSIPES POWDER FROM PANTE RIEK FOR PB2+ ION ADSORPTION - Mirna Rahmah Lubis (Jurnal Teknik Kimia USU, 2014)
Adsorption capacity was calculated in Eichornia crassipes adsorbent. In several areas of Aceh province such as Meulaboh, Takengon, and Tamiang, people extirpate Eichornia crassipes because it is considered disturbing water flow. Therefore, this research tries to investigate the utilization of Eichornia crassipes so that it could be used as bioadsorbent in order to reduce heavy metal from waste water. The main obejctive of this research is to reduce lead content, and to determine the best condition of lead adsorption in solution by using Eichornia crassipes powder. The analysis is conducted by using Atomic Adsorption Spectrophotometer. Research result indicates that optimum adsorption occurs at solution with pH of 4.4, lead concentration of 40 mg/L, and contact time of 75 minutes. Lead adsorption by Eichornia crassipes biomass follows adsorption isotherm of Langmuir and pseudo-second order with capacity of adsorption (am) of 27,78 mg/g, and adsorption constant (K) is 12 L/mg.